Cold Days a Novel of the Dresden Files - Butcher, Jim (New York : Roc, 2012)
Following his death by a mystery assailant, Harry Dresden, Winter Knight to Mab, the Queen of Air and Darkness, must gather his friends and allies, prevent the annihilation of countless innocents, and find a way out of his eternal subservience before his newfound powers claim the only thing he has left to call his own ... his soul.
"A Roc book".
Keywords: Dresden, Harry (Fictitious character); Wizards; Magic; Chicago (Ill.); Fantasy fiction